Фунціональні біотехнологічні агенти Bacillus Thuringiensis для контролю популяції колорадського жука - Бойко, Марія Вікторівна (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата сільськогосподарських наук зі спеціальності 03.00.20 «Біотехнологія». Національний університет біоресурсів і природокористування України. Київ, 2019. Дисертацію присвячено дослідженню біологічної дії ентомопатогенних бактерій Bacillus thuringiensis та розробленню технологічних параметрів отримання препаративних форм на їх основі для контролю чисельності колорадського жука. За результатами комплексу досліджень біологічних особливостей нового штаму ентомопатогенних бактерій Bacillus thuringiensis 87/3 оптимізовано біотехнологічні етапи його культивування і отримання сучасних препаративних форм для контролю чисельності Leptinotarsa decemlineata Say. Оптимізовано середовище з додаванням капустяного гідролізату, яке дає можливість отримати за 48 год культивування високий вихід життєздатних клітин (титр спор складає до 4,4 млрд/мл культуральної рідини). Показано, що культура штаму Bacillus thuringiensis 87/3 має високий потенціал технологічності (титр метаболітного споро-кристалічного комплексу складає від 3,6 до 4,8 млрд/мл культуральної рідини), ентомоцидності (99,1 %) та антифунгальної дії, яка виявляється у зменшенні кількості уражених листків паршею яблуні в 1,5–2 рази, порівняно із контрольним варіантом, що розширює можливості використання біоагента. Економічно обґрунтовано ефективність біотехнології отримання рідких препаративних форм на основі Bacillus thuringiensis 87/3 для контролю фітофагів в агроценозах, що підтверджено рентабельним виробництвом (рівень 56,6 %), максимальним рівнем прибутку у технології вирощування картоплі у варіанті за внесення Bacillus thuringiensis, який складає 82562 грн.
Thesis for awarding the candidate degree in agricultural sciences by specialty 03.00.20 «Biotechnology». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2019. The thesis is devoted to the study of the entomopathogenic bacteria Bacillus thuringiensis biological action and the development of technological parameters for the preparation of preparative forms based on them to control the number of the Colorado potato beetle (Leptinotarsa decemlineata Say.). In thesis the physiological, culture-morphological, molecular-biological, and biochemical properties of Bt 87/3 strain were studied. The conducted researches open prospects of Bt 87/3 strain using in the agricultural practice with the further receiving technologies development of the biopreparation polyfunctional type of action. The molecular-biological analysis of the Bt 87/3 strain was carried out, based on the study of the 16S rRNA nucleotide sequences genes polymorphism. Based on the analysis of the 16S rRNA nucleotide sequence, a dendrogram of phylogenetic connections between different representatives of the bacteria genus Bacillus was constructed. The 16S rRNA strain sequence was registered and entered into the GenBank database (MH719010). The nutrient medium for cultivation was optimized by the composition of sources of carbon and nitrogen feed, as well as on the content of micro elements. We used the cabbage broth as the basis for preparing the nutrient medium. Using mathematical method of experiment planning, the nutrient medium was optimized for the B. thuringiensis 87/3 cultivation in the conditions of biolabs low tonnage production. The nutrient medium optimization was carried out in the alternation of the maximum and minimum values contents of the media components. Optimum concentrations were investigated in the medium of carbon source (15 g/l of glucose), nitrogen (10 g/l of corn extract) and content of phosphorus-containing inorganic salts (1,5 g/l of diamonium phosphate). The results of the studies indicate that optimized medium provides the ability to obtain a high yield of viable cells in 48 hours of cultivation (the titre of the metabolic spore-crystalline complex is up to 4,4 billion/ml of culture liquids). The nutrient medium proposed composition is much cheaper than laboratory medium, which are widely used for cultivation microorganisms of this species and can be recommended for using in laboratory and production conditions. In the conditions of Chernihiv Polissya, field studies of the Bacillus thuringiensis 87/3 strain entomocidal activity against Leptinotarsa decemlineata Say larvae were conducted. It was found that the Bacillus thuringiensis 87/3 liquid formulation was equally active against larvae of 1‒2 ages and young imago. Bacillus thuringiensis 87/3 functional activity showed that by the action of entomotoxic metabolites there was a decrease in nutritional activity, metamorphosis and growth (weight relative to control 53,4 %). The phytophagus death occurs on the third day after treatment, and the maximum effect – after seven days. The field investigation results indicate a high biological efficacy of Bacillus thuringiensis liquid formulations on the colorado potato beetle larvae – 99,4 %. At the same time the potato yield was in variants with Bacillus thuringiensis 87/3 – 31 t/ha, with chemical insecticide Patriot – 28 t/ha. There was an increase in tubers biomass. Under the action of Bacillus thuringiensis 87/3, tubers mass occurred due to the formation of a larger fraction (in 1,3–2,0 times as compared with control) and a decrease in the number and mass of small tubers (2–4 times). It was shown that aksenic culture strain B. thuringiensis 87/3 after in vitro selection has high potential of efficiency (titer metabolic spore-crystal complex is from 3,6 to 4,8 billion/ml culture fluid) insecticidal (98,4 %) and antifungal action, which manifested in changes of Venturia ssp. micromycetes morphogenesis in particular expression of specific lysis zones, change the density, thickness, the growth direction of mycelium and the inhibition of conidia germination within 86‒93 %. The difference in the degree of inhibitory effect of the B. thuringiensis strains culture liquid on phytopathogenic test culture Fusarium spp. was demonstrated. Thus, the retarding of conidia germination ranged from 54,0 to 60,0 % with appropriate mycelium browning. The metabolites of spore-forming bacteria, besides the entomocidal activity against phytophages have appeared to be of considerable interest as for the microbial interaction and as the basis of the preparations of the multifunctional actions. It is economically justified that phytoprotection based on Bacillus thuringiensis 87/3 in the colorado beetle control system allows more efficient using of energy resources in agricultural production (the field effectiveness of the biological preparation on potato plants will be about 82562 UAH compared with chemical preparations; profitability level of production 56,6 %)
Keywords: Bacillus thuringiensis 87/3; споро-кристалічний комплекс; оптимізація поживного середовища; глибинне культивування; цільовий продукт; ентомоцидна активність; Leptinotarsa decemlineata Say; spore-crystal complex; nutrient medium optimization; deep cultivation; target product; entomocidal activity